26Al–26Mg chronology and oxygen isotope distributions of multiple melting for a Type C CAI from Allende. (15th November 2015) - Kawasaki, Noriyuki; Kato, Chizu; Itoh, Shoichi; Wakaki, Shigeyuki; Ito, Motoo; Yurimoto, Hisayoshi
Abstract: Disequilibrium oxygen isotopic distributions of Ca–Al-rich inclusions (CAIs) correspond to multiple melting events in the solar nebula. 26 Al– 26 Mg systematics may be applicable for age differences among such melting events. We have carried out a coordinated study of detailed petrographic observations and in-situ oxygen and magnesium isotope measurements for a Type C CAI, EK1-04-2, from the Allende CV3 meteorite to determine the melting events and their ages. The CAI consists mainly of spinel, anorthite, olivine, and pyroxene, and has a core and mantle structure. Petrography of the core suggests that the crystallization sequence of the core minerals is from spinel, anorthite, olivine, and to pyroxene. The mantle has the same mineral assemblage as the core, and shows incomplete melting and solidification textures. Oxygen isotopic compositions of the minerals are distributed along the carbonaceous chondrite anhydrous mineral (CCAM) line (δ 18 O = −44‰ to +9‰), which indicates to preserve a chemical disequilibrium status in the CAI. Spinel shows a 16 O-rich signature (δ 18 O ∼ −43‰), while anorthite is 16 O-poor (δ 18 O ∼ +8‰). Olivine and pyroxene in the core have the same oxygen isotopic composition (δ 18 O ∼ −15‰), which indicates their equilibrium. Olivine and pyroxene in the mantle have variable oxygen isotopic compositions and are slightly depleted in 16 O (δ 18 O = −13‰ to −4‰) compared with the same minerals in the core. The 26 Al– 26 Mg systematics is consistent with the disequilibrium status observed according to the petrography and oxygen isotopes. Spinel is plotted on a line of ( 26 Al/ 27 Al)0 = (3.5 ± 0.2) × 10 −5, anorthite is plotted on a line of (−1 ± 5) × 10 −7, and olivine and pyroxene in the core are plotted on a line of (−1 ± 7) × 10 −6 . Plots of olivine and pyroxene in the mantle are scattered below the isochron of these minerals in the core. This study indicates that the EK1-04-2 Type C CAI underwent multiple heating events after the formation of its CAI precursor. The precursor CAI was formed ∼0.4 Myr after the formation of the Solar System defined by canonical CAI formation. At least 1.6 Myr after the precursor CAI formation, the CAI was partially melted and the melt exchanged oxygen isotopes with surrounding 16 O-poor nebular gas. 16 O-poor olivine and pyroxene in the core crystallized from the melt. Subsequently, Al-rich chondrules accreted onto the CAI, and the CAI experienced partial melting again and recrystallized to form the mantle. The oxygen and magnesium isotopes in anorthite were redistributed during thermal metamorphism in the Allende parent body. Our study reveals that the CAI had been retained in the solar nebula for at least 1.6 Myr and underwent multiple melting events in the nebula, and oxygen and 26 Al– 26 Mg systematics has been partially disturbed depending on crystal sizes by metamorphism on the parent body.